SISTEM DROPSHIP DALAM BISNIS ON LINE DAN SOLUSINYA DALAM HUKUM ISLAM - Habib Masyhudi (MIYAH : Jurnal Studi Islam, 2020)
Abstract: Online business creates smart buyers because buyers can freely compare the price of a product or service without moving from one place to another. Dropshipping is the sale of products that allow dropshippers to sell goods to customers with photos from suppliers or stores (without having to provide goods) and sell at prices determined by the dropshipper or a joint price agreement between the supplier and the dropshipper. When a new transaction model emerged in society, some fiqh experts linked this activity to just one contract, namely 'aqd al-buyu (sale and purchase contract). In fact, a transaction should be linked to several other contracts that have the same form. There are differences in buying and selling in general with the dropship system, generally in buying and selling there is a meeting between the seller and the buyer, so in buying and selling with the dropship system the meeting is not held. Judging from the transactions made, buying and selling with the dropship system allows using the samsarah, salam, wakalah bil ujrah and murabahah contracts. And for the validity of dropship with this approach, in practice it must meet the requirements set and not contradict Islamic law.Kata kunci: Dropship, Hukum Islam